Strategi Bertahan Pasar Ternak Palangki Dalam Tinjauan Historis - Felia Siska; Irwan Irwan (Jayapangus Press, 2020)
Palangki cattle market has been established since 1996. The market has become the largest cattle market in West Sumatra. Buyers in the Palangki cattle market are not only people from West Sumatra Province but also people outside West Sumatra Province such as the people of Jambi, Riau, Jakarta, Bengkulu and other areas. The purpose of this study is to analyze the development and survival strategies of the Palangki cattle market since 1996-2018. The theory used is a survival strategy by Edi Suharsono. Research uses a qualitative approach and historical research methods. The stages in historical research are heuristics that as gathering data or sources, verification or source criticism, interpretation or giving meaning and historigraphy. Research results show that the Palangki livestock market has developed quite rapidly from the local market to become a regional market in type A. The market viability strategy is supported by the development of extensive infrastructure, livestock buying and selling systems using the